Primary studies of the composition of distillate beverages produced from Sorbus Domestica fruits - Galabova Mariana; Stoyanov Nikolay; Mitev Panko (BIO Web of Conferences, 2022)
S. domestica are valuable plants which have been used for both nutritional purposes and in traditional medicine. Recent studies reveal that in the fruits of S. domestica the sugar content and total acidity is similar to quantities in apples (Malus spp.) and pears (Pyrus spp.). Despite the sufficient data obtained S. domestica is not yet so strongly represented in the production of distilled beverages. For the purpose of this study, we obtained beverages by means of three different methods - distillation of fermented juice (A), distillation of fermented crushed fruit mixture (B) and distillation of ethanol-water extract (C). The different fractions obtained during the distillation process were studied and correspondently used to determine the quantities of Alcohol, Esters, Aldehydes, Higher alcohols and Methanol. Concentration of Esters in the fractions is between 3688.0 mg/L to 29.0 mg/L. The quantity of Esters in fractions of Series A and B is three times higher than in Series C. Regarding the Aldehyde and Higher alcohols content is ten times higher in both A and B Series in comparison to Series C.